(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
River sediment movement is a crucial and intricate process. Knowing the types and quantities of sediment delivered by rivers is crucial for effective water management. This paper presents a comprehensive review on the analysis the sediment distribution in the region (upstream and downstream Kufa barrage), verify the numerical model results (Such as HEC-RAS, SSIIM, Mike and another models) via the measurement data (field and laboratory data) from river. Advantages, disadvantages, the river morphology (Examine the fluctuations produced by the existence of the dam) the reproduction of model processes and practical applications were discussed. Most of sediment studies did not fully cover sediment transport problems because of the complex character of sediment transport and its different conditions.